FEMINIST PERSPECTIVES IN ELIF SHAFAK’S NOVELS: A CRITICAL DISCOURSE ANALYSIS - Irfan Ashraf; Dr. Noreen Saba (International Premier Journal of Languages & Literature, 2026)
The present study aims to explore the feminist views of Elif Shafak’s novels Forty Rules of Love (2010), Three Daughters of Eve (2016) and The Island of Missing Trees (2021) in the context of critical discourse analysis. The study explores the representation of gender, women’s autonomy, and social conventions in different cultures in these texts. Using qualitative methods including thematic analysis and discourse analysis, the study shows Shafak’s ability to weave personal and collective histories to challenge patriarchal constructs and promote gender equality. The findings suggest that her novels are effective in fostering feminist discourse, empathy and understanding across cultural boundaries. The study highlights her contribution to social change and gender justice, on the importance of embracing ambiguity and multiple truths. Further investigation on her impact on feminist discourse and intercultural dialogue through literature is recommended.